Multi-user virtual environments for the classroom practical approaches to teaching in virtual worlds - Vincenti, Giovanni, 1978-; Braman, James, 1981- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book highlights cutting-edge teaching ideas using theoretical discussions, case studies, and experiments pertaining to virtual environments, including learning foreign languages in virtual environments and examples that encourage educators to design and develop new worlds of learning inside and outside the university"--Provided by publisher.